Kaji Eksperimen Alat Angkat Bantu Kerja (Sistem Pneumatik) Untuk Lepas/Pasang Roda Kendaraan - Johannes Munintja Mawa; Adriyan Warokka; Franklin Bawano (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2022)
Work safety and comfort is something that must be seriously considered in an industry in general, as well as in after-sales service workshops for vehicles / wheels - 4. In their daily work, mechanics, especially for removing / lowering and installing / raising the wheels of vehicles that are being treated still using muscle. The way of working as above is still not safe and comfortable for mechanics. For this reason, applied research is carried out in order to obtain a solution for mechanics, namely in the form of work aids. The work lifting tool is designed by modifying the trolley where the existing work equipment is by adding a pneumatic system that functions to lower and raise the wheels of vehicles that are in the process of maintenance and repair. This research begins with surveys and data collection, structural design, design of a series of pneumatic systems, structural manufacturing and pneumatic systems, testing the ability of working lifting equipment and the following results are obtained: Air pressure: 4 (bar), Lifting load (maximum): 50 (kg), lifting time: 7 (seconds). Actuator diameter 63 (mm) with a thrust / lift force of 1100 (N). With the Pneumatic system work lifting equipment, a sense of security and comfort for mechanics at work can be achieved.